Clinical Study of Incomplete Cervical Dilation in Dairy Cattle and Buffaloes - Sagar, Ram; Saxena, Atul; Kumar, Sharad; Kumar, Sudhir (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
A total of 17 clinical cases of cows and buffaloes suffering from incomplete cervical dilation (ICD) were included in the study. Among these cases, 35.29% and 64.71% cases were observed in cows and buffaloes, respectively. Pluripara were more affected as compared to primiparous animals. Treatment procedures adopted in these cases were mechanical manipulation of the cervix and a combination of four drugs (PGF2α, Betamethasone, Estrogen, and Valethamate bromide). All the animals responded to the treatment protocol. The combined hormonal treatment (PGF2α, Betamethasone, Estrogen, and Valethamate bromide) was suitable for managing incomplete cervical dilation.